Combination disease‐modifying treatment in spinal muscular atrophy: A proposed classification - Proud, Crystal M.; Mercuri, Eugenio; Finkel, Richard S.; Kirschner, Janbernd; De Vivo, Darryl C.; Muntoni, Francesco; Saito, Kayoko; Tizzano, Eduardo F.; Desguerre, Isabelle; Quijano‐Roy, Susana; Benguerba, Kamal; Raju, Dheeraj; et al. (Annals of Clinical and Translational Neurology, 2023)
We sought to devise a rational, systematic approach for defining/grouping survival motor neuron ‐targeted disease‐modifying treatment (DMT) scenarios. The proposed classification is primarily based on a two‐part differentiation: initial DMT, and persistence/discontinuation of subsequent DMT(s). Treatment categories were identified: monotherapy add‐on, transient add‐on, combination with onasemnogene abeparvovec, bridging to onasemnogene abeparvovec, and switching to onasemnogene abeparvovec. We validated this approach by applying the classification to the 443 patients currently in the RESTORE registry and explored the demographics of these different groups of patients. This work forms the basis to explore the safety and efficacy profile of the different combinations of DMT in SMA.